2017
DOI: 10.1016/j.semcdb.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

How cells channel their stress: Interplay between Piezo1 and the cytoskeleton

Abstract: Cells constantly encounter mechanical stimuli in their environment, such as dynamic forces and mechanical features of the extracellular matrix. These mechanical cues are transduced into biochemical signals, and integrated with genetic and chemical signals to modulate diverse physiological processes. Cells also actively generate forces to internally transport cargo, to explore the physical properties of their environment and to spatially position themselves and other cells during development. Mechanical forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(199 citation statements)
references
References 75 publications
9
160
0
Order By: Relevance
“…Indeed, a mechanically-activated protein has recently been shown to have a more expanded constriction pore in the presence of a positive mismatch (thicker lipids) than in negative mismatch (thinner lipids) [62]. Third, GM1-enriched domains appear dependent on the anchorage through ankyrin (our unpublished data) and the cytoskeleton is known to modulate Piezo1 activity [63].…”
Section: Lipid Domains As Modulators Of Piezo1 and Pmca Membrane Locamentioning
confidence: 73%
“…Indeed, a mechanically-activated protein has recently been shown to have a more expanded constriction pore in the presence of a positive mismatch (thicker lipids) than in negative mismatch (thinner lipids) [62]. Third, GM1-enriched domains appear dependent on the anchorage through ankyrin (our unpublished data) and the cytoskeleton is known to modulate Piezo1 activity [63].…”
Section: Lipid Domains As Modulators Of Piezo1 and Pmca Membrane Locamentioning
confidence: 73%
“…McHugh et al (2010) have shown that Piezo1 channels localize to the endoplasmic reticulum (ER) in epithelial cells where they can regulate integrin-mediated cell adhesion via calpain and talin activation. Therefore, Piezo1 channels can regulate intracellular Ca 2+ concentrations via Ca 2+ release from intracellular stores or through the formation of mechanically-gated ion channels in the outer cell membrane (Nourse & Pathak, 2017). Interestingly, Piezo1 is also voltage sensitive (Moroni, Servin-Vences, Fleischer, Sanchez-Carranza, & Lewin, 2018) and, therefore, its repertoire of known functions in CNS neurons and glial cells, both in health and disease, is likely to increase in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by biophysical studies that Piezo1 is sensitive to specific lipid types 14 and the observations that Piezo1 is diffusively localized in plasma membranes of many cell lines with very few interaction partners identified 4,13,15,16 . However, an open question In the regulation of Piezo1 is the intimate involvement of the integrin-linked actin cytoskeleton in Piezo1's functions 17 . Before the discovery of Piezo1 as a mechanosensitive ion channel, Piezo1 was shown to be involved in integrin activation 18 .…”
Section: Introductionmentioning
confidence: 99%